Bortezomib, melphalan, and dexamethasone for light-chain amyloidosis - Kastritis, Efstathios; Leleu, Xavier; Arnulf, Bertrand; Zamagni, Elena; Cibeira, María Teresa; Kwok, Fiona; Mollee, Peter; Hájek, Roman; Moreau, Philippe; Jaccard, Arnaud; Schönland, Stefan; Filshie, Robin; et al. (Journal of clinical oncology, 2020)
Purpose: Oral melphalan and dexamethasone (MDex) were considered a standard of care in light-chain (AL) amyloidosis. In the past decade, bortezomib has been increasingly used in combination with alkylating agents and dexamethasone. We prospectively compared the efficacy and safety of MDex and MDex with the addition of bortezomib (BMDex). Methods: This was a phase III, multicenter, randomized, open-label trial. Patients were stratified according to cardiac stage. Patients with advanced cardiac stage (stage IIIb) amyloidosis were not eligible. The primary end point was hematologic response rate at 3 months. This trial is registered with ClinicalTrials.gov identifier NCT01277016. Results: A total of 109 patients, 53 in the BMDex and 56 in the MDex group, received ≥ 1 dose of therapy (from January 2011 to February 2016). Hematologic response rate at 3 months was higher in the BMDex arm (79% v 52%; P = .002). Higher rates of very good partial or complete response rates (64% v 39%; hazard ratio [HR], 2.47; 95% CI, 1.30 to 4.71) and improved overall survival, with a 2-fold decrease in mortality rate (HR, 0.50; 95% CI, 0.27 to 0.90), were observed in the BMDex arm. Grade 3 and 4 adverse events (the most common being cytopenia, peripheral neuropathy, and heart failure) were more common in the BMDex arm, occurring in 20% versus 10% of cycles performed. Conclusion: BMDex improved hematologic response rate and overall survival. To our knowledge, this is the first time a controlled study has demonstrated a survival advantage in AL amyloidosis. BMDex should be considered a new standard of care for AL amyloidosis.
Gesehen am 19.04.2021